Children, families and schools : developing partnerships for inclusive education - Beveridge, Sally (RoutledgeFalmer, 2005)
This book is concerned with home-school relations from an 'inclusive'perspective, in that it addresses questions common to all schools, but with an emphasis on children with special needs.- Resumé vydavatel